Movimento Nursing Now no Brasil: trajetórias e perspectivas - Marchiori, Gianna Fiori; Contim, Divanice; Molina, Nayara Paula Fernandes Martins (Revista Família, Ciclos de Vida e Saúde no Contexto Social, 2021)
.